Inspired Imperfection : How the Bible's Problems Enhance Its Divine Authority - Boyd, Gregory A., 1957- (Book collections on Project MUSE., 2020)
"In Inspired Imperfection, Gregory A. Boyd adds another counterintuitive and provocative thesis to his corpus. While conservative scholars and pastors have struggled for years to show that the Bible is without errors, Boyd considers this a fool's errand. Instead, he says, we should embrace the mistakes and contradictions in Scripture, for they show that God chose to use fallible humans to communicate timeless truths. Just as God ultimately came to save humanity in the form of a human, God chose to impart truth through the imperfect medium of human writing. Instead of the Bible's imperfections being a reason to attack its veracity, these 'problems' actually support the trustworthiness of Christian Scripture. Inspired Imperfection is required reading for anyone who's questioned the Bible because of its contradictions."--